2015
DOI: 10.4238/2015.july.27.18
|View full text |Cite
|
Sign up to set email alerts
|

Expression of LTP genes in response to saline stress in rice seedlings

Abstract: ABSTRACT. Saline stress is one of the primary factors limiting increased rice productivity in the southern region of Brazil. Farming can be affected by salinity that is due to both the origin of the soils as well as the irrigation water. Lipid transfer proteins (LTPs) have many physiological functions, including in the response to saline stress. Therefore, the objective of this study was to quantify the relative expression of 11 genetic isoforms that encode LTP1-type proteins in rice genotypes tolerant and sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Lipid transfer proteins (LTPs) play an important role in abiotic stress tolerance [89], and can facilitate the inter-membrane exchange and transfer of various amphiphilic molecules including phospholipids, glycolipids, steroids, acyl-CoAs, and fatty acids [90]. Transcript levels of LTPs increased in response to drought [91], salt [92] and cold [93] and the increase of non-specific lipid-transfer protein 1 expression in tolerant genotypes give more support to its role of increasing tolerance to abiotic stress.…”
Section: Resultsmentioning
confidence: 99%
“…Lipid transfer proteins (LTPs) play an important role in abiotic stress tolerance [89], and can facilitate the inter-membrane exchange and transfer of various amphiphilic molecules including phospholipids, glycolipids, steroids, acyl-CoAs, and fatty acids [90]. Transcript levels of LTPs increased in response to drought [91], salt [92] and cold [93] and the increase of non-specific lipid-transfer protein 1 expression in tolerant genotypes give more support to its role of increasing tolerance to abiotic stress.…”
Section: Resultsmentioning
confidence: 99%
“…Apoplastic barriers such as suberin lamellae protect against uncontrolled flow of water and solutes under abiotic stresses [1]. Responsiveness of LTP genes to drought and salinity stress [5,6] implies an involvement in stress adaptation. Nevertheless, importance of LTPs for suberin deposition under drought is mentioned only rarely [1,7], whilst no attempt seems to have been made to relate LTP-dependent formation of apoplast barriers to salt stress responses even though enhanced deposition of suberin and lignin in apoplastic root barriers is an important component of salt tolerance [8].…”
Section: Introductionmentioning
confidence: 99%
“…Gao et al ( 2008 ) introduced the LTP gene into potato plants and found that the gene functions in the resistance to salt and drought. Moraes et al ( 2015 ) studied the tolerance and disease resistance genotypes of 11 genetic isoforms of rice LTP1 proteins, and Wang et al ( 2014 ) found that LTP3 could be overexpressed in transgenic Arabidopsis under thermotolerance. It was reported that the cis ‐regulatory elements of the NtLTP genes in Nicotiana sylvestris promoters were involved in abiotic stress and phytohormone responsiveness (Yang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%